(untitled) (Experimental biology, 2015)
This article describes the results of the study the level of physical development of young people, in an amount of 100 people from different regions of Kazakhstan, enrolled in schools in Almaty and the Kazakh National University, at the age of 17 to 25 years. Found that individuals in a population of youth age groups I and II are signifi cant differences in the value of indicators of anthropometric parameters. Average growth in young men standing in group I, represented in the sample are statistically higher than a 2.3% increase in young people’s group II. Iindeks in the scheme of somatotipirovaniya M.Chernorutskomu showed that among boys of group I was dominated by individuals with normastenicheskim physique 68%. Among the boys of group II with 76% normostenichesky. The index of morphine showed that the boys I and II prevailed dolihomorfny body type.